Prevalence and intensity of trichodinids and monogeneans on farmed tilapia in southwestern Mexico - Osuna-Cabanillas, Juan M.; Medina-Guerrero, Rosa M.; Camacho-Zepeda, Selena; Morales-Serna, Francisco N.; Fajer-Ávila, Emma J. (Ecosistemas y Recursos Agropecuarios, 2022)
Small-scale tilapia production contributes to sustainable rural development; however, it can be stagnated due to parasite diseases. This work aimed to determine the prevalence and intensity of infection of trichodinids and monogeneans on farmed tilapia in rural areas of Guerrero, Oaxaca and Chiapas, located in southwestern Mexico. A total of six trichodinid (Trichodina centrostrigeata, T. compacta, T. heterodentata, T. magna, T. nigra y Trichodina sp.) and nine monogenean (Cichlidogyrus cirratus, C. dossoui, C. halli, C. mbirizei, C. sclerosus, C. thurstonae, C. tilapiae, Gyrodactylus cichlidarum y Scutogyrus longicornis) species were identified. The findings of C. mbirizei y C. cirratus represent new geographic records for Mexico. Trichodinid and monogenean infections occurred, respectively, at 73 and 93 % of farms, distributed in coastal areas and mountain valleys. The prevalence of trichodinids was high (60–100 %) in 30 % of farms, whereas the median intensity was <10 trichodinids per fish. The prevalence of monogeneans was high and median intensities ranged between 1 and 30 at most farms. These results suggest that parasites can potentially occur everywhere; therefore, better management practices should be implemented to prevent parasite outbreaks.